Intestinal mesenchymal cells regulate immune responses and promote epithelial regeneration in vitro and in dextran sulfate sodium‐induced experimental colitis in mice. (21st June 2021) - Hidalgo‐Garcia, Laura; Molina‐Tijeras, José Alberto; Huertas‐Peña, Francisco; Ruiz‐Malagón, Antonio Jesús; Diez‐Echave, Patricia; Vezza, Teresa; Rodríguez‐Sojo, María Jesús; Morón, Rocío; Becerra‐Massare, Patricia; Rodríguez‐Nogales, Alba; Gálvez, Julio; Rodríguez‐Cabezas, María Elena; et al.
Abstract: Aim: Disruption of the intestinal mucosal tolerance, that is, the immunological unresponsiveness to innocuous food antigens and the commensal microbiota, in the colon is associated with several chronic diseases including inflammatory bowel disease (IBD). Understanding the mechanisms responsible for intestinal mucosal tolerance has potential translational value for its therapy and management. Human intestinal mesenchymal cells (iMCs) play important roles in colonic mucosal tolerance, but further studies on their tissue regenerative and immunomodulatory capacities are necessary in order to fully understand their function in health and disease. Methods: In this study, we have isolated and analysed the capacity of human iMCs to promote wound healing and modulate immune responses in vitro and in vivo, using the dextran sulfate sodium (DSS)‐induced colitis model. Results: Cultured iMCs were CD45 − CD73 + CD90 + CD105 + and accelerated the wound closure in a normal colon mucosa (NCM) 356 human epithelial cell wound healing assay. Furthermore, iMCs blocked the LPS‐mediated induction of TNF‐α in THP‐1 macrophages and inhibited the proliferation of peripheral blood mononuclear cells, partly through the induction of indoleamine‐2, 3‐dioxygenase. In DSS colitic mice, iMCs administration reduced the disease activity index and ameliorated intestinal tissue damage and permeability. Furthermore, iMCs reduced intestinal inflammation, evidenced by a decreased mRNA expression of pro‐inflammatory cytokines, reduced IL‐1β secretion by intestinal explants and inhibited colonic iNOS protein expression. Conclusions: Our data show that human iMCs isolated from the noninflamed intestine possess tissue‐regenerative and immunomodulatory capacities that could potentially be harnessed/restored in order to reduce IBD severity.